Non-tariff measures and exports: The Malaysian case / Arumugam G. Sithamparam - Arumugam G., Sithamparam (2017)
This study examines the effect of non-tariff measures (NTMs) on the Malaysian exporters. Motivated by the paucity of studies in this area, this study investigates the predicament of the exporters with regard to the main NTMs faced and whether the measures impede or enhance exports; and vary across markets. It examines the significance of stringency of NTMs, including specific measures, on export intensity. Demographic variables used are type, ownership, age, and size of firms. The study also investigated the response decisions (exit, loyalty or voice concerns in reactive or proactive manner) pursued by the Malaysian exporters when faced with NTMs, the NTM types experienced by exporters, and whether information asymmetry is significantly related to exports. Two analytical approaches were used namely, 1) gravity model for data extracted from the Trade Analysis and Information System (TRAINS) database for the 2001-2013 period, and 2) multinomial logistics regression on data obtained through a survey of 143 export firms between June 2014 and December 2014. The key findings reveal that tariffs and NTMs in importing countries exert opposite effects on Malaysian exports and greater NTM coverage of exports in the importing country promotes the Malaysian exports. Agricultural and industry products as well as their major export markets - ASEAN, EU, and Japan found NTMs had positive effects. Dual effects (impede and enhance) of NTMs were found in EU market. The key findings from the survey data inform firms that find NTMs as stringent are those: exporting less than 75 percent of goods; small and medium size compared to large firms; resource-based firms exporting less than 75 percent; exporting less than 75 percent to the US, EU and Japan. Similar findings were reached for stringency of technical measures (TM) and stringency of private measures (PM). Stringency of customs procedures (CP) experienced in the US, EU, Japan, and ASEAN. Other non-tariff measures (ONTMs) were found to be not stringent in most export iv markets, except in Japan. Firms experienced information asymmetry for exports to the US and EU markets. Price effects, quantity reduction, and quality restrictions are experienced by the exporters in the US, EU and Japanese markets. Firms across all export levels (4 export levels- “25 percent and less”, “26-50 percent”, “51-75 percent” and “more than 75 percent”) adopt loyalty response strategy in a reactive manner when faced with NTMs. Resource-based firms mostly pursue a loyalty-reactive strategy. Firms that export “25 percent and less” adopt the exit strategy when faced with NTMs more than firms in other export levels. Firms with less than 5 years in operation actively adopt all three response strategies in a reactive manner - “exit-reactive”, “loyalty-reactive” and “voice-reactive”. This study contributes to the existing empirical literature on NTM effects on trade from the perspective of a middle income and highly trade dependent economy. It also sheds light on the stringency of the impact of NTMs on exports from Malaysia.